2014
DOI: 10.1038/ncomms5613
|View full text |Cite
|
Sign up to set email alerts
|

Trans-ethnic genome-wide association study of colorectal cancer identifies a new susceptibility locus in VTI1A

Abstract: The genetic basis of sporadic colorectal cancer (CRC) is not well explained by known risk polymorphisms. Here we perform a meta-analysis of two genome-wide association studies in 2,627 cases and 3,797 controls of Japanese ancestry and 1,894 cases and 4,703 controls of African ancestry, to identify genetic variants that contribute to CRC susceptibility. We replicate genome-wide statistically significant associations (P < 5×10−8) in 16,823 cases and 18,211 controls of European ancestry. This study reveals a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 26 publications
0
69
0
Order By: Relevance
“…The narrow-sense heritability estimates based on twin and family studies of CRC range from 12 to 35% 2,3 . Although several genome-wide association studies (GWAS) of CRC have successfully identified common single-nucleotide polymorphisms (SNPs) associated with CRC risk 421 , a large fraction of the heritability still remains elusive 22 . Our GWAS combines data from four large CRC consortia, the Colorectal Cancer Transdisciplinary (CORECT) Study, the Colon Cancer Family Registry (CFR), the Molecular Epidemiology of Colorectal Cancer (MECC) Study and the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO) to elucidate previously undiscovered susceptibility loci for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The narrow-sense heritability estimates based on twin and family studies of CRC range from 12 to 35% 2,3 . Although several genome-wide association studies (GWAS) of CRC have successfully identified common single-nucleotide polymorphisms (SNPs) associated with CRC risk 421 , a large fraction of the heritability still remains elusive 22 . Our GWAS combines data from four large CRC consortia, the Colorectal Cancer Transdisciplinary (CORECT) Study, the Colon Cancer Family Registry (CFR), the Molecular Epidemiology of Colorectal Cancer (MECC) Study and the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO) to elucidate previously undiscovered susceptibility loci for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The residual disparity could be explained by factors that were not controlled in the analyses. SEER data do not collect information on other potentially important confounder such as the uses of over-the-counter medications and oral prescription drugs 56 , provider- and facility-related characteristics 57 , as well as genetics 58 , dietary 59 , environmental 60 , and biological factors 17 . A more complete assessment of major underlying factors is needed in order to inform the development of strategies that can further reduce or even completely eliminate the racial disparity in colon cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Standard marker exclusion criteria were applied in each cancer consortium (511), and we have previously reported the summary of QC details in Hung et al (12). Genotype imputation was conducted for each cancer site using IMPUTE, BEAGLE, MACH and Minimac (imputation threshold of R 2 > 0.3) using the 1000 genome reference panel.…”
Section: Methodsmentioning
confidence: 99%
“…Logistic regression analysis using a log additive model was performed previously to test variant associations with cancer risk for the forty-five studies (511), providing per-allele odds ratios (ORs) adjusted for age, principal components and gender where applicable. Study-specific results were then combined for each cancer site using a fixed effects model.…”
Section: Methodsmentioning
confidence: 99%